Impact of Climate Changes on Marine Environments - Zielinski, Tymon (Springer, 2015)
This book contributes to the current discussion on global environmental changes by discussing modifications in marine ecosystems related to global climate changes. In marine ecosystems, rising atmospheric CO2 and climate changes are associated with shifts in temperature, circulation, stratification, nutrient input, oxygen concentration and ocean acidification, which have significant biological effects on a regional and global scale.